HUBUNGAN PARITAS DAN OBESITAS DENGAN KEJADIAN PREEKLAMPSIA PADA IBU HAMIL DI RUMAH SAKIT UMUM DAERAH KOTA PRABUMULIH TAHUN 2023: Indonesia - Lestari, Diah Ayu; Nesa Ayu Murthisari Putri (Jurnal Kesehatan dan Pembangunan, 2025)
Preeclampsia is a disease with signs of high blood pressure, namely blood pressure ?140/90 mmHg and proteinuria ? 300 mg/24 hours, tissue swelling, and the presence of protein in the urine (proteinuria) that occurs due to pregnancy. The purpose of this study was to determine the relationship between parity and obesity with the incidence of preeclampsia in pregnant women at the Prabumulih City Regional General Hospital in 2023. The research method was analytical with a Cross Sectional approach. The population was all pregnant women who were treated in the obstetrics room of the Prabumulih City Regional General Hospital in 2023. Sampling used the Random Sampling technique. The research instrument was a checklist. Based on the results of the study of 57 respondents who had high-risk parity and were diagnosed with preeclampsia as many as 47 (15.7%) while respondents who had low-risk parity and were diagnosed with preeclampsia as many as 60 (20%) and from 66 respondents who were obese and diagnosed with preeclampsia as many as 48 (16%) while respondents who were not obese and diagnosed with preeclampsia as many as 59 (19.7%). The conclusion is that there is a significant relationship between parity and the incidence of preeclampsia with a Pvalue of 0.005 <? 0.05 and there is a significant relationship between obesity and the incidence of preeclampsia with a Pvalue of 0.000 <? 0.05